2011
DOI: 10.1063/1.3622609
|View full text |Cite
|
Sign up to set email alerts
|

Dust accumulation effect on efficiency of Si photovoltaic modules

Abstract: We experimentally studied the electrical efficiency effects of naturally forming atmospheric dust deposits on commercial photovoltaic panels. The variable considered for measurements was the electric potential for three commercial silicon modules: monocrystalline, polycrystalline, and amorphous. A mathematical model was developed to determine maximum potential as a function of temperature and of total incident radiation. The study presents two essential parts: the naturally deposited dust particles and the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(35 citation statements)
references
References 6 publications
3
31
0
1
Order By: Relevance
“…These larger particles are in the atmosphere and depositing, but are not being included in the measurements of airborne particulates or the calculations of deposition. Previous experiments on solar energy systems have seen a peak in deposited size distributions around 20 mm (Roth and Anaya 1980;Biryukov 1996;Cabanillas and Mungu ıa 2011), indicating that these larger particles are present and significant.…”
Section: Comparison Between Observations and Modelmentioning
confidence: 84%
“…These larger particles are in the atmosphere and depositing, but are not being included in the measurements of airborne particulates or the calculations of deposition. Previous experiments on solar energy systems have seen a peak in deposited size distributions around 20 mm (Roth and Anaya 1980;Biryukov 1996;Cabanillas and Mungu ıa 2011), indicating that these larger particles are present and significant.…”
Section: Comparison Between Observations and Modelmentioning
confidence: 84%
“…Comparative studies of different PV module technologies performance under varied climatic conditions were reported [8,12,13]. Dust effect on the power output of PV modules and the dust particles distribution were investigated by Cabanillas and Munguia [14]. In the current study, PV modules of known power ratings were exposed to outdoor atmospheric condition for several months in Dhahran, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, Elminir et al [18] observed a reduction in PV output power up to 17.4 % per month in a separate field experiment in Egypt during the months of December 2004 to June 2005 while Kymakis et al [19] monitored the performance of a PV park in Crete for one year and they found out the soiling losses were 4-5 % during the winter and 6-7 % during the summer period. Cabanillas et al [20] observed a reduction of modules power up to 13 % within 3 months in Mexico. On the other hand, experimental investigation on the reduction of the PV output efficiency presented in [21] shows that the reduction of efficiency reached up to 11.6 % when the dust deposition density was fixed at about 8 gm -2 .…”
Section: Dustmentioning
confidence: 97%